Pre-Service Physical Education Teachers’ Perceptions of Anticipated Challenges and Needs during Teacher Education Programs - de Guise, Audrey-Anne; Girard, Stéphanie; Boulanger, Maude (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2024)
Given that teacher dropout is an issue for beginning teachers, it is important to be proactive in order to retain teachers within the profession. Physical Education pre-service teachers’ education programs represent a crucial part of their professional development in preparing them to face the challenges that often explain retirement, especially students’ motivation. Authors recognize the importance of considering pre-service teachers’ needs during teacher education programs and their concerns about the challenges to be faced once they start teaching (Richards et al., 2013). Using a qualitative approach, this study aims to: (1) identify pre-service Physical Education teachers’ perceptions of anticipated challenges in general, (2) identify the specific challenges they anticipate about supporting students’ motivation and (3) describe how they can be prepared to support students’ motivation. Participants consisted of 18 pre-service Physical Education teachers (Mage = 25; SD = 3.61 years) from French-language universities in Quebec (Canada). Four focus groups were conducted, and data were analyzed consistent with the four steps suggested by Boutin (2007). Results indicate that the main challenges anticipated by pre-service Physical Education teachers are classroom management and students’ lack of motivation. In terms of supporting students’ motivation, five specific challenges were highlighted: (1) student heterogeneity, (2) proposal of learning activities to support motivation, (3) student engagement, (4) management of disengaged students, and (5) gender differences. As for their needs during teacher education program, participants wished to learn how to plan motivational strategies, be given more opportunities to practice, and discuss how to implement these strategies. Recommendations for teacher education programs are discussed in the conclusion.